Analisis Komentar Negatif Kelangkaan Minyak Goreng pada Akun Instagram @megawatisoekarnoputri.id - Muthmainnah Muthmainnah; Savira Noerroslina; Rama Reinaldo Aran; Farida Hariyati (MUKASI: Jurnal Ilmu Komunikasi, 2023)
Technology has progressed massively, providing people to access information very quickly. Some citizens, misuse these technological developments to slander others, they are not reflecting as good internet users, for the example they used sarcasm to comment on others to express their thoughts. This study aims to analyze negative comments on @megawatisoekarnoputri.id Instagram account which include: a) Form, b) Meaning, and c) Purpose. This research is descriptive qualitative research. The data were collected by analyzing Instagram comments from @megawatisoekarnoputri.id account. The data are all facts, words and sentences contained in the comments column of @megawatisoekarnoputri.id's Instagram account which contains negative elements. The data were collected using the method of reading and note-taking, especially the method of free reading with the following stages: 1. Search / data search, 2. Attention / listening and paying attention, 3. Copy paste / taking screenshots or copying, 4. Transcript / transcribing data. The data analysis technique utilized a qualitative descriptive technique with stages, including: 1. Identification, 2. Classification, 3. Description, 4. Analysis. The results of this research are: (1) The form of sarcasm consists of: word form and sentence form. (2) The purposes of sarcasm are: satirizing and swearing, insulting or mocking. (3) Sarcasm consists of several meanings contained in it such as: connotative meaning, denotative meaning, contextual meaning.